Trophic niche of a neustonic copepod community sustained by local production in high- and low-salinity summer water masses in the northeastern East China Sea - Choi, Jang Han; Kang, Yoonja; Kang, Chang-Keun; Soh, Ho Young (Frontiers in Marine Science, 2024)
We investigated the trophic dynamics between neustonic copepod communities and particulate organic matter (POM) sourced from contrasting water masses, i.e., high- and low-salinity areas, within the northeastern East China Sea. The sampling of neustonic copepod communities occurred three times in the summer (June, August, and September) of 2021, and considered the influx of the Yangtze River Diluted Water (YRDW) and the extension of the Tsushima Warm Current (TWC). To examine the relationship between the neustonic copepods and surface POM, we employed stable isotope techniques. Surprisingly, the neustonic copepod community exhibited a reluctance to feed on surface POM. The neustonic copepod community in the YRDW-dominated area in August showed higher δ13C values than those in the TWC-dominated area. The trophic groups within the neustonic copepod population appeared to consume selectively depending on the individual preferred prey sizes and composition. Using the POM from the water masses that affected the food sources consumed by neustonic copepods, we found a strong dependence on prey items originating from the TWC. This result suggests that the marine neustonic copepod community does not rely significantly on food sources derived from riverine freshwater.